Developing a fuzzy automated targeting methodology for water conservation in batch processes - Nun, Sophanna (Animo Repository, 2010)
Recent environmental trends have made the process industries adopt the reuse/recycle strategy to reduce their waste as well as to use the resources more efficiently. In order to define the target of fresh water consumption and wastewater generation and to synthesize reuse/recycle water network in process industries, two major approaches have been used namely pinch based and mathematical optimization approaches. In this research work, the hybrid automated targeting technique for batch process (Foo, 2010) is further developed by including fuzzy optimization to analyze the uncertainty trade-off between storage capacity and minimum target of fresh water consumption. Five case studies are analyzed using this newly developed technique. Among the Pareto-optimal solutions found by using the method of Foo (2010), fuzzy optimization developed in this thesis work can effectively find the best compromise solution between storage capacity and minimum target of fresh water consumption that should be implemented in the project of process integration or cleaner production when the space limitation is faced. This technique can assist the decision makers in the process industries to identify strategies for water conservation in batch processes